Analysis of heat transfer on MHD Jeffrey nanofluid flow over nonlinear elongating surface of variable thickness. Issue 2 (15th November 2021) - Ali, Aamir; Maqsood, M.; Anjum, H. J.; Awais, M.; Sulaiman, M.
Abstract: Due to its vast application in the engineering discipline, nanofluids have become a popular subject of investigation in the mathematical and physical research. The enhancement of thermal conductivity is a peculiar feature of nanofluids. The fluid model being investigated in the current study is the Jeffrey nanofluid commonly found in many industrial processes such as lubrication, natural gas networks, spray processes, cooling of nuclear reactors and many others. We study the heat transfer affects on the flow of a Jeffery non‐Newtonian fluid with submersed nanoparticles, in the presence of applied magnetic field, along a nonlinear stretchable surface, discussing features such as Brownian and thermophoresis diffusion. The effects of viscous dissipation, ohmic heating and thermal radiation on the flow characteristic have also been analyzed. Solution for the nondimensional boundary value problem have been obtained numerically by considering the effects of non‐Newtonian fluid parameter. The graphical illustration of the obtained results highlights the effects of numerous physical parameters on the flow dynamics in terms of fluid velocities, thermal profiles and nanoparticles concentration. Abstract : Due to its vast application in the engineering discipline, nanofluids have become a popular subject of investigation in the mathematical and physical research. The enhancement of thermal conductivity is a peculiar feature of nanofluids. The fluid model being investigated in the current study is the Jeffrey nanofluid commonly found in many industrial processes such as lubrication, natural gas networks, spray processes, cooling of nuclear reactors and many others.…